ESTIMATE AND ANALYSIS OF VOCATIONAL TRAINING SCHOOL (IEK) STUDENTS’ SATISFACTION REGARDING THE QUALITY OF STUDIES PROVIDED BY THESE SCHOOLS - Sofia ANASTASIADOU; Thomas FOTIADIS; Lazaros ANASTASIADIS; George IAKOVIDIS; Xristina FOTIADOU; Chrysanthi TILIAKOU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2016)
Measuring students’ satisfaction renders great service to the post-secondary educational institutions, since it offers the possibility to detect the strengths and weaknesses of these institutions and determine the areas that should be improved. Students’ satisfaction goes beyond teachers’ evaluation, which is a short sighted perspective, and includes wider concepts of students’ learning experience. In this context, knowing the degree of satisfaction is not enough. What is rather important is to comprehend the factors contributing to this satisfaction. The present survey aims at revealing the causes leading to IEK students’ satisfaction or obstructing it. The research was carried out at IEK of West Macedonia, Greece and the research tool used was SEVQUAL. Moreover, Analyse des Correspondences was used for data analysis. Results relating to students’ satisfaction and quality of studies were not encouraging. Finally, problems affecting the quality of studies came forward.